PEER AND AUTOMATED WRITING EVALUATION (AWE): INDONESIAN EFL COLLEGE STUDENTS’ PREFERENCE FOR ESSAY EVALUATION - Ginting, Rita Seroja; Fithriani, Rahmah (LLT Journal: A Journal on Language and Language Teaching, 2022)
A plethora of studies have investigated the effects of peer evaluation (PE) and automated writing evaluation (AWE) on the writing products and perspectives of English as a foreign language (EFL) students. However, few studies compare students' preferences regarding its utilization to evaluate their essays. This study aimed to determine which method EFL college students prefer for evaluating the quality of their English academic writing. For data collection, a questionnaire was distributed to determine the frequency with which students utilize feedback. Twenty students enrolled in English Education completed the questionnaire. The open-ended interview was then administered to three students in order to gain a deeper understanding of their perspectives on these two modes of evaluation. Frequency count and thematic analysis were utilized to analyze the data. The results indicate that students favor using peer feedback over Grammarly, the AWE software used in this study, for two reasons. First, they view their peers as their real audience, and second, they value their peers' comments more than Grammarly's. However, Grammarly also received positive point as the students enjoys writing with this tool. Therefore, it is believed that the combination of these two s will result in the most essay writing progress.